Lithium Disilicate Ceramics in Prosthodontics: Unveiling Innovations, Current Trends, and Future Horizons - Reddy, N Simhachalam; Sreenivasulu, Duggineni; Bekkem, Divya (International Journal of Dental Materials, 2023)
In contemporary dentistry, ceramic restorations have experienced a surge in popularity. This paper aims to review the current state of literature and recommendations concerning the application of lithium disilicate glass-ceramic IPSTM e.Max. This comprehensive review also covers material science, mechanical intricacies, and optical properties of glass-ceramic material. Further, this review extends valuable clinical insights, presenting recommendations for the effective utilization of IPS e.Max CAD restorations in dental practices.